(untitled) (Archives of Mechanics - Test, 2010)
The paper investigates the reflection-transmission process of acoustic waves, generated by an inhomogeneous fluid layer of finite thickness, which is sandwiched between two semi-infinite homogeneous half-spaces. First a direct problem is solved by determining the reflection and transmission coefficients along with the wave solution in the layer, produced by a known incident wave. Owing to the planar stratification of the layer, the unknown acoustic pressure is looked at as a generalized plane wave. Upon the Fourier transformation, the second-order wave equation is written as a firstorder system of equations for the dependence on the depth of the pressure and the partial derivative. The corresponding Volterra integral equation gives the pressure in the layer as a series of repeated integrals of powers of the pertinent depth-dependent matrix of the system. The reflection and transmission coefficients of the layer are then determined for any incidence angle. Next an inverse problem is investigated. The derivatives of the reflection coefficient, with respect to the frequency, are shown to provide the thickness of the layer, the speed beyond the layer and the moments, of any order, of the refractive index.